Investigate Students’ Attitudes toward Computer Based Test (CBT) at Chemistry Course - zabadi, Abdelrahim (Archives of Business Research, 2016)
Computer Based Assessment (CBT) is being a highly widespread method to assess students’ fulfillment at the university level. This study seeks to examine the attitude of the students towards computer-based test (CBT) at the KAU-Saudi Arabia Jeddah. Quantitative approach using survey questionnaire was adopted to carry out the current study using convenience-sampling technique. The sample consists of (60) undergraduate students who had taken the exam on CBT were selected from college of science-chemistry department to examine their perceptions towards CBT. To achieve this aim, the researchers examine the possibility of using student feedback in the effectiveness of this method in assessment. The findings show that: the majority of respondents have positive attitude towards CBT, (83.7%) of students said they were competent with the use of computer due to their prior experience. Regarding test administration, they reported that there are some errors in the chemical equations, formulas, construction in the exam sections, and inadequate time. Nevertheless, they achieved the exam successfully and reached satisfaction through CBT features such as direct scoring, validity, and transparency in grading. The bottom line, CBT experience will become favorable for students and then will earn its effectiveness in the context of assessments methods.